Diabetes mellitus service preparedness and availability: a systematic review and meta-analysis - Alie, Melsew Setegn; Girma, Desalegn; Adugna, Amauel; Negesse, Yilkal (Frontiers in Endocrinology, 2024)
In areas with limited resources, the lack of preparedness and limited availability of diabetes mellitus services in healthcare facilities contribute to high rates of illness and death related to diabetes mellitus. As a result, this study focuses on analyzing the combined prevalence of preparedness and availability of diabetic services in countries with limited resources.Methods: A comprehensive search was conducted across various databases, such as PubMed/MEDLINE, Web of Science, Google Scholar, and African Journal Online. The search aimed to identify primary research articles that assessed the availability and preparedness of services for individuals with specific type 2 diabetes mellitus. The articles included in the search spanned from January 2000 to February 23, 2024. To analyze the data, a meta-analysis of proportions was performed using the random-effects model. Additionally, the researchers assessed publication bias by examining a funnel plot and conducting Egger's test. Heterogeneity and sensitivity analyses were also conducted to evaluate the data. The findings of the study regarding the pooled prevalence of diabetes service preparedness and availability, along with their corresponding 95% confidence intervals, were presented using a forest plot.A comprehensive analysis was conducted on 16 research articles focusing on service preparedness and 11 articles examining service availability. The sample sizes for these studies were 3,422 for service preparedness and 1,062 for service availability. The findings showed that the pooled prevalence of diabetes service preparedness was 53.0% (95% CI: 47.0-60.0). Furthermore, in this systematic synthesis the overall pooled prevalence of service availability for diabetes mellitus was 48% (95% CI: 36.0-67.0), with highest pooled prevalence observed in Asia, with a pooled prevalence of 58% (95% CI: 38.0-89.0).Our study reveals a significant disparity in the preparedness and availability of services for diabetes mellitus, which falls below the minimum threshold set by the WHO. These findings should capture the attention of policymakers and potentially serve as a foundation for reevaluating the current approach to diabetes service preparedness and availability. To enhance the availability and preparedness of diabetes services, a tailored, multifaceted, and actionoriented approach to strengthening the health system is required.